Acute effect of breathing exercises on muscle tension and executive function under psychological stress - Liang, Wen-Ming; Xiao, Jing; Ren, Fei-Fei; Chen, Zi-Shuai; Li, Chun-Ri; Bai, Zhen-Min; Rukšenas, Osvaldas (Frontiers in Psychology, 2023)
Intensive and long-lasting office work is a common cause of muscular and mental disorders due to workplace stressors. Mindful and slow breathing exercises decrease psychological stress and improve mental health, whereas fast breathing increases neuronal excitability. This study aimed to explore the influence of 5 min of mindful breathing (MINDFUL), slow breathing (SLOW), fast breathing (FAST), and listening to music (MUSIC) on muscle tension and executive function during an intensive psychological task. Forty-eight participants (24 men and 24 women) were enrolled. Muscle tension was recorded using surface electromyography, and executive function was assessed using the Stroop Color and Word Test (Stroop Test). The respiration rate (RR), oxygen saturation (SpO2), end-tidal carbon dioxide (EtCO2), and the subjects’ preferred method were also recorded. During the experiment, participants performed a one-time baseline test (watching a neutral video for 5 min) and then completed 5 min of MUSIC, MINDFUL, SLOW, and FAST in a random sequence. The Stroop Test was performed after each intervention, including the baseline test, and was followed by a 5 min rest before performing the next intervention. None of the methods significantly influenced muscular activity and performance of the Stroop Test in both men and women, based on the average 5 min values. However, at the fifth minute, men’s accuracy rate in the Stroop Test was significantly higher after SLOW than after MUSIC and FAST, and the reaction time after the SLOW was the shortest. SpO2 was significantly higher during SLOW than during MUSIC, and RR was relatively lower after SLOW than after MUSIC. Most men preferred SLOW, and most women preferred MUSIC, whereas FAST was the most unfavorable method for both men and women. In conclusion, brief breathing exercises did not substantially affect muscle tension under psychological stress. SLOW has greater potential for sustaining executive function in men, possibly via its superior respiration efficiency on SpO2 and inhibition of RR.